Advantages and disadvantages of using podcasts in learning English online - Jumanova, Sabrina (The Lingua Spectrum, 2025)
English language teaching occupies an important place in the modern education process. Today, English is widely used not only in academic fields but also in everyday life. Therefore, the process of learning English requires the use of many methods and resources. One of the most effective methods of teaching English is interactive methods. These methods encourage students to actively participate and increase their interest. For example, group discussions, role plays, and other interactive activities play an important role in developing students’ language skills. Through these methods, students not only learn the language, but also understand the cultural context. To be successful in teaching English, teachers must make their lessons interesting and effective. This, in turn, increases students’ interest in the language and makes their learning process more effective. It is also important for teachers to help students set and achieve their goals. The use of podcasts in learning English online provides new opportunities and approaches in the modern educational process. Podcasts are information presented in audio format that help make the learning process more interesting and interactive. This article provides information on the pros and cons of using podcasts.